Characterizing the microbiota of cleft lip and palate patients: a comprehensive review - Gershater, Elizabeth; Liu, Yuan; Xue, Binglan; Shin, Min Kyung; Koo, Hyun; Zheng, Zhong; Li, Chenshuang (Frontiers in Cellular and Infection Microbiology, 2023)
Orofacial cleft disorders, including cleft lip and/or palate (CL/P), are one of the most frequently-occurring congenital disorders worldwide. The health issues of patients with CL/P encompass far more than just their anatomic anomaly, as patients with CL/P are prone to having a high incidence of infectious diseases. While it has been previously established that the oral microbiome of patients with CL/P differs from that of unaffected patients, the exact nature of this variance, including the relevant bacterial species, has not been fully elucidated; likewise, examination of anatomic locations besides the cleft site has been neglected. Here, we intended to provide a comprehensive review to highlight the significant microbiota differences between CL/P patients and healthy subjects in various anatomic locations, including the teeth inside and adjacent to the cleft, oral cavity, nasal cavity, pharynx, and ear, as well as bodily fluids, secretions, and excretions. A number of bacterial and fungal species that have been proven to be pathogenic were found to be prevalently and/or specifically detected in CL/P patients, which can benefit the development of CL/P-specific microbiota management strategies.